Radial and vertical velocity field in a steady state symmetric tropical storm - MANDAL, J.C. (MAUSAM, 1997)
ABSTRACT. A method to construct a consistent structure of steady state symmetric tropical storms from a few known values of temperature anomaly in the centre and around it has been developed. The role of kinematic eddy coefficient of viscosity in producing the transverse circulation in a tropical storm has been tested and discussed. The well known features and characteristics of a tropical storm, such as, eyewall, sinking motion, inside the eyewall, low-level radial inflow and high level outflow are well produced in the model. The computation shows that there is an increase of transverse circulation with increase of the magnitude of eddy coefficient. In the boundary layer, the vertical eddy coefficient plays more important role than the radial eddy coefficient; while in the upper layer the latter is much more important than the former. It has also been found that in absence of radial exchange coefficient, there can be no sinking motion in the central region of the storm. The magnitude of radial and vertical wind in the eye region is more sensitive to the variation of radial eddy coefficient. In addition to the eddy coefficients, transverse circulations also depend upon the tangential wind distribution above the boundary layer.